1997
DOI: 10.2960/j.v22.a17
|View full text |Cite
|
Sign up to set email alerts
|

Cetacean Interactions with Trawls: A Preliminary Review

Abstract: Cetaceans interact with trawls to an undetermined extent. A preliminary review of global data indicates that individuals of 25 cetacean species (two mysticete, 23 odontocete) have been documented to have died in working trawls or discarded trawling gear. Cetacean interactions with trawls are complex, in part because both fishermen and cetaceans are drawn to areas of high prey density. Furthermore, within such areas, cetaceans are probably often attracted to trawling activities because they make it easier for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
155
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 9 publications
8
155
0
4
Order By: Relevance
“…Such a mechanism, particularly in oligo trophic ecosystems, is related not only to the direct consumption of feed pellets around the fish cages, but also, and principally, to the increase in primary production through released nutrients and a rapid transfer of these nutrients up the food web, with a strong influence on the coupling between pelagic and benthic compartments (Belias et al 2003, Machias et al 2006, Pitta et al 2009). Bottlenose dolphins are known to be opportunistic allowing them to adapt to changes in prey availability (Shane et al 1986, Bearzi et al 2008b and to take advantage of human activities by either following fishing boats to feed on discarded fish (Fertl & Leatherwood 1997, Bearzi et al 1999, by catching/ stealing fish during fishing operations (Diaz López 2006, Lauriano & Bruno 2007, Gonzalvo et al 2008, or by feeding near fish farm facilities (Díaz López & Bernal Shirai 2007, Bearzi et al 2009). This feeding strategy has most likely been adopted by bottlenose dolphins to increase their feeding rate, while decreasing the energy expenditure associated with foraging (Fertl & Leatherwood 1997), in order to compensate for the lack of fish prey in the surrounding waters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mechanism, particularly in oligo trophic ecosystems, is related not only to the direct consumption of feed pellets around the fish cages, but also, and principally, to the increase in primary production through released nutrients and a rapid transfer of these nutrients up the food web, with a strong influence on the coupling between pelagic and benthic compartments (Belias et al 2003, Machias et al 2006, Pitta et al 2009). Bottlenose dolphins are known to be opportunistic allowing them to adapt to changes in prey availability (Shane et al 1986, Bearzi et al 2008b and to take advantage of human activities by either following fishing boats to feed on discarded fish (Fertl & Leatherwood 1997, Bearzi et al 1999, by catching/ stealing fish during fishing operations (Diaz López 2006, Lauriano & Bruno 2007, Gonzalvo et al 2008, or by feeding near fish farm facilities (Díaz López & Bernal Shirai 2007, Bearzi et al 2009). This feeding strategy has most likely been adopted by bottlenose dolphins to increase their feeding rate, while decreasing the energy expenditure associated with foraging (Fertl & Leatherwood 1997), in order to compensate for the lack of fish prey in the surrounding waters.…”
Section: Discussionmentioning
confidence: 99%
“…Bottlenose dolphins are known to be opportunistic allowing them to adapt to changes in prey availability (Shane et al 1986, Bearzi et al 2008b and to take advantage of human activities by either following fishing boats to feed on discarded fish (Fertl & Leatherwood 1997, Bearzi et al 1999, by catching/ stealing fish during fishing operations (Diaz López 2006, Lauriano & Bruno 2007, Gonzalvo et al 2008, or by feeding near fish farm facilities (Díaz López & Bernal Shirai 2007, Bearzi et al 2009). This feeding strategy has most likely been adopted by bottlenose dolphins to increase their feeding rate, while decreasing the energy expenditure associated with foraging (Fertl & Leatherwood 1997), in order to compensate for the lack of fish prey in the surrounding waters. Recent studies have demonstrated how overfishing has caused detrimental effects on fish stocks in the study area , Gonzalvo et al 2010, including important prey of bottlenose dolphins (Bearzi et al 2010a).…”
Section: Discussionmentioning
confidence: 99%
“…Al though trawls affect a large number of different species of marine mammals, they generally have a lower level of impact than gillnets (see Fertl & Leatherwood 1997). However, in certain situations they can be a major problem.…”
Section: Risks From Different Fishing Techniquesmentioning
confidence: 99%
“…This has been documented, for example, for Hector's dolphins (Rayment & Webster 2009) and PRE Sousa, which are known to follow trawlers in unusually large groups (Jefferson 2000). Mothers with calves may be particularly drawn to fishing operations because they have higher energetic demands, putting them and especially their calves at greater risk of entanglement (Fertl & Leatherwood 1997). A disproportionate preference by mothers for feeding in association with pair trawlers is suspected for PRE Sousa (Jefferson 2000, Hung 2008.…”
Section: Behavioural Responses To Prey Aggregationmentioning
confidence: 99%
“…The significance of cetacean mortality in trawl nets (e.g., Couperus 1997;Fertl and Leatherwood 1997;Dans et al 1997;Crespo et al 1994Crespo et al , 1997Crespo et al , 2000 and longlines (Crespo et al 1997) has only recently begun to be recognized. As an example, recent pulses in strandings of dolphins (particularly short-beaked common and Atlantic white-sided dolphins; Delphinus delphis and Lagenorhynchus acutus, respectively) on the western and northern coasts of Europe have coincided Figure 3.…”
Section: Incidental Mortality In Fisheries (Bycatch)mentioning
confidence: 99%